ANALYSING RIVERBED MORPHOLOGY AS A RESPONSE TO CHANGES OF GEOLOGICAL AND NEOTECTONIC CONDITIONS: A CASE STUDY OF THE OĽŠAVA RIVER - Barabas, Dušan; Tkáč, Matúš (Quaestiones Geographicae, 2019)
The morphological examination of the Slovak Oľšava River channel and valley parameters is based on observation of changes in the troughs’ longitudinal profile. While the relationship between valley and channel parameters has previously been researched, establishment of the diverse conditions in trough formation enables better understanding of the basin/riverbed relationship. Our research is based on field measurements of representative sections of nine segments defined by changes in the longitudinal profile. The field measurements were performed in autumn months during a low water period to ensure the best conditions for repeated measurements. Significantly, as much as 75% asymmetry of the measured flow encourages the assumption of strong tectonic influence on the riverbed formation. While the difference between the assumed continuous changes of measured parameters and the actual measured or evaluated parameters remains a matter of interpretation, the detected anomalies enable interpretation of the parameters’ relationships. The river bed and the valley morphological parameters were evaluated on the model of The Olšava River basin which drains the eastern part of the Košická kotlina Basin (the Toryská pahorkatina Upland). The location of the basin at the foot of the Slanské vrchy Mts. is an important factor in the formation of the river network asymmetries. Both the Neogene contact between the Slanské vrchy Hills neo-volcanites and the Toryská pahorkatina Upland and the neo-tectonics influenced the change in morphological parameters in the valley’s longitudinal and transverse profile and the Oľšava river bed. Our terrain works comprised length and width measurements of the bars, their positions in the river bed, the width and depth of the channel and the type of section riffle. Available maps enabled calculation of the following; ratio of valley height to width, average gradient of the section, stream gradient index, average channel segment slope, the degree of sinuosity and the highest observed correlation between slope, river segment type (0.9576) and the width and type river reach (−0.9089). High correlation coefficient values were recorded for the valley height and width ratio, the type of river section, the water area and the total river bed width and area.